To graph the equation \( x - y = 6 \) using the slope-intercept form \( y = mx + b \), we first need to rewrite the equation.
Starting with: \[ x - y = 6 \] we can isolate \( y \): \[ -y = -x + 6 \] Multiplying everything by -1 gives us: \[ y = x - 6 \]
Now, we can identify the slope \( m \) and the y-intercept \( b \):
- The slope \( m = 1 \).
- The y-intercept \( b = -6 \).
This means the line crosses the y-axis at the point \( (0, -6) \).
To find another point on the line, we can use the slope. Since the slope is 1, for each increase of 1 in \( x \), \( y \) also increases by 1.
Starting at the y-intercept \( (0, -6) \):
- If \( x = 1 \), then: \[ y = 1 - 6 = -5 \] So another point is \( (1, -5) \).
With two points, \( (0, -6) \) and \( (1, -5) \), you can plot the line on a graph.
Among the given responses, the illustration that shows the points \( (0, -6) \) and \( (1, -5) \) corresponds to the equation \( y = x - 6 \). Thus, the correct answer is the first illustration you described, which shows a line passing through the points \( (0, -6) \) and \( (1, -5) \).